Hysteretic phenomena and switching effects under phase transitions in external field - Stefanovich, L. I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The field dependence of the order parameter is investigated theoretically, using a statistical approach within the framework of the Ginzburg-Landau model with respect to the ferroelectric phase transition. It is found that, along with the existence of ordinary non-switching hysteresis in not too high fields e(e&lt&ltec, where ecis the coercive field), hysteresis of a switching type can be observed at the fields in excess of the coercive one.